Habituelle Abortneigung: rationale Diagnostik und Therapie - Beuter-Winkler, Petra; Germeyer, Ariane; Wallwiener, Lisa-Maria; Toth, Bettina (Der Gynäkologe, 2012)
Recurrent miscarriage (RM) affects 1-3% of couples during childbearing years worldwide and influences the life balance of patients and partners. So far, possible risk factors could be detected in up to 50% of RM patients including anatomical malformations, infectious diseases, endocrine dysfunctions, genetic anomalies, acquired and inherited thrombophilia as well as (auto) immune disorders. Treatment strategies and options consist of surgical interventions, preimplantation genetic diagnosis, hormonal treatment and anticoagulant as well as immunomodulatory medication. This review will focus on established and new diagnostic and therapeutic options and discuss current literature.